Bay11-7082 facilitates wound healing by antagonizing mechanical injury- and TNF-α-induced expression of MMPs in posterior cruciate ligament. (4th July 2019) - Xu, Chunming; Zhang, Yanjun; Sutrisno, Linawati; Yang, Li; Chen, Rongfu; Sung, K. L. Paul
ABSTRACT: Purposes: To investigate the ability of synoviocytes (SCs) in regulating MMPs expression in the posterior cruciate ligament fibroblasts (PCLfs) after TNF-α treatment, to test whether a specific inflammation inhibitor Bay11-7082 can antagonize the expression of MMPs in PCLfs after injury. Methods : The microenvironment of knee joint cavity after PCL injury was mimicked in an in vitro co-culture system. The effects of TNF-α treatment on the expression of MMPs in PCL fibroblasts (PCLfs) were studied. The expression of MMPs mRNA and protein was detected by qRT-PCR and western blot. For the in vivo study, the Bay11-7082 inhibitor was injected into the knee joint cavity after injury, and then were performed on histological analysis. Results : In the mono-culture conditions, 6% mechanical injury upregulated the expression of MMP-2, whereas downregulated MMP-1 and -3, additionally 12% mechanical injury were upregulated all. However, in co-culture conditions, 6% and 12% both significantly increased MMPs expressions. Stretch injury and TNF-α treatment significantly upregulated expression of MMPs mRNA and protein levels in mono-cultured PCLfs. This effect was more significant in PCLfs Plus SCs co-culture system, in which the cells were treated by combination of stretch injury and TNF-α. In addition, Bay11-7082, a specific inflammation inhibitor, could significantly decrease the expression of MMPs induced by stretch injury and/or TNF-α treatment. Less infiltrated inflammatory cells and more integrated tissues were detected in injury PCL 2 weeks after Bay11-7082 treatment, compared to injury group. Immunofluorescent staining showed very low expression levels of MMPs in PCL of Bay11-7082-treated group, compared to the injury groups. Conclusions : SCs sever as the supporting cells that aggravate the TNF-α-induced MMPs accumulation in PCLfs. Inhibition of the expression of MMPs by Bay11-7082 is a promising way to facilitate the self-healing of PCL.